2015
DOI: 10.1002/eat.22398
|View full text |Cite
|
Sign up to set email alerts
|

Apps and eating disorders: A systematic clinical appraisal

Abstract: ObjectiveSmartphone applications (apps) are proliferating and health‐related apps are particularly popular. The aim of this study was to identify, characterize, and evaluate the clinical utility of apps designed either for people with eating disorders or for eating disorder professionals.MethodA search of the major app stores identified 805 potentially relevant apps, of which 39 were primarily designed for people with eating disorders and five for professionals.ResultsThe apps for people with eating disorders … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
85
0
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(93 citation statements)
references
References 7 publications
3
85
0
4
Order By: Relevance
“…What is welcome is the fact that this is an active research field with interventions being put to the test. This is in stark contrast to the paucity of research on the multitude of smartphone applications designed for people with eating disorders, a form of modern technology that, similar to eTherapy, has the potential to do harm as well as good [37].…”
Section: Resultsmentioning
confidence: 88%
“…What is welcome is the fact that this is an active research field with interventions being put to the test. This is in stark contrast to the paucity of research on the multitude of smartphone applications designed for people with eating disorders, a form of modern technology that, similar to eTherapy, has the potential to do harm as well as good [37].…”
Section: Resultsmentioning
confidence: 88%
“…Mobile technology has the capacity to deliver evidence-based weight loss interventions with lower cost and burden than traditional intervention models. However, studies report that their potential is yet to be realized [5]. A recent literature review of mobile technology interventions illustrates the limited use of mobile technology, mainly text messaging, in such interventions [6].…”
Section: Introductionmentioning
confidence: 99%
“…Although mobile technology is pervasive in society, our participants remained unsure of its potential in clinical work. Further, there is often an assumption in the literature that clinicians are technologically literate and using published evaluative tools prior to prescription of mHealth apps (Fairburn & Rothwell, 2015;Aungst et al, 2014;Hussain e al., 2015;Donker et al, 2013). Other relevant studies have revealed tools to evaluate mHealth apps are predominantly unknown and underused in clinical practice (Butcher et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Recognising this, Fairburn & Rothwell (2015) suggest that clinicians should enquire about their clients' mHealth app use during initial assessments. This sets the expectation that clinicians are familiar with and knowledgeable about mHealth apps in their field of practice.…”
Section: Disclosuresmentioning
confidence: 99%